Peranan visual infografis pada surat khabar / Deden Maulana A dan Hari Nugraha - Deden, Maulana A; Hari, Nugraha (Universiti Teknologi MARA, Perak, 2017)
Information graphic and why do newspapers need them ? - information graphics exploit any combination of drawings, word and photographic images to create a visual means whereby news and feature coverage is extended in order to help newspaper reader toward a fuller understanding of the words on the page. Information graphics are essential in the newspaper. First the growth of a sophisticated communications industry has created a visually literate reading public. They are a powerful weapon in the battle for public attention and loyality. Secondly, information graphic save space, for newspaper jurnalist space is at a premium anything which allows them to exploit the available editorial columns to the best advantage will be welcomed. The diagram, as far as we know, first appeared in manuscripts, many early diagrams are concerned with structures and links, frequently connected with philosophical concept. Interlinked circles, circles linked by curve and family tree form were all used. Our main hypothesis is that new technologies such as the popularization of personal computer and the internet has consolidated and increased the use of infographics that today are basic part of contemporary journalism, particulary in scientific journalism. It is a new and important language for journalist and the public in general. Good editorial graphics need to fulfil creteria common to good information graphics. Sound understanding of the readership profile will establish the most suitable treatment to promote the message. If the readership includes profesional people and the socially upwardly-mobile, one can afford to use a sophisticated and fashionable image